Actualización Tecnológica Y Puesta En Servicio Del Banco De Entrenamiento Del Plc Siemens S7-200 Del Laboratorio De Automatización De La Universidad Antonio Nariño En Cartagena (2023)
The purpose of this project was the update and commissioning of the Siemens S7-200 PLC training bench of the Automation and Control Laboratory of the Antonio Nariño University of Cartagena. To achieve this objective, a methodology was proposed that included the collection of information on the current conditions of the training bench, the design of the comprehensive automatic control system, the implementation of the system and the evaluation of the project